2012
DOI: 10.1371/journal.pone.0049514
|View full text |Cite
|
Sign up to set email alerts
|

Secretory Vesicles Are Preferentially Targeted to Areas of Low Molecular SNARE Density

Abstract: Intercellular communication is commonly mediated by the regulated fusion, or exocytosis, of vesicles with the cell surface. SNARE (soluble N-ethymaleimide sensitive factor attachment protein receptor) proteins are the catalytic core of the secretory machinery, driving vesicle and plasma membrane merger. Plasma membrane SNAREs (tSNAREs) are proposed to reside in dense clusters containing many molecules, thus providing a concentrated reservoir to promote membrane fusion. However, biophysical experiments suggest … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
50
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 35 publications
(55 citation statements)
references
References 51 publications
4
50
1
Order By: Relevance
“…Syntaxin was C-terminally labelled, resulting in EGFP being on the outside of the plasma membrane. Note that an N-terminal fusion where EGFP is adjacent to the Habc domain has been reported to be excluded from the docking site 68 . Munc18-EGFP rescues hormone secretion after siRNA-mediated knockdown of Munc18-1 and Munc18-2 in PC12 cells 18 .…”
Section: Methodsmentioning
confidence: 99%
“…Syntaxin was C-terminally labelled, resulting in EGFP being on the outside of the plasma membrane. Note that an N-terminal fusion where EGFP is adjacent to the Habc domain has been reported to be excluded from the docking site 68 . Munc18-EGFP rescues hormone secretion after siRNA-mediated knockdown of Munc18-1 and Munc18-2 in PC12 cells 18 .…”
Section: Methodsmentioning
confidence: 99%
“…[12] Next, cell cultures of two types of cells (AtT-20 and HEK-293 cells) were monitored for aprolonged period of time,w hich showed that the cells maintained their high viability ( Figure S5), demonstrating that the hydrogel is mechanically strong enough to provide physical support for the encapsulated cells,n on-toxic to cells,a nd permeable for nutrients,which are desirable properties for the long-term use of cell cultures.…”
Section: Methodsmentioning
confidence: 99%
“…However, the strongest colocalization is with vesicles and PI(4,5)P 2 domains (30–50%) rather than with syntaxin-1 clusters. Additional live cell studies monitoring PI(4,5)P 2 , syntaxin-1 and vesicle exocytosis are needed to assess this especially since there are reports that secretory vesicles localize to sites of low SNARE density [84]. The exact function of syntaxin-1 clusters in vesicle exocytosis is currently unclear [85].…”
Section: Protein Effectors Of Pi(45)p2 Utilized In the Secretory mentioning
confidence: 99%